Effect of Combination Herbal Plants Extracts on Diabetes Mellitus - Semesta, Cleopatra Diva; Putri, Refitha Nurul; Hadisaputri, Yuni Elsa (Indonesian Journal of Biological Pharmacy, 2023)
Diabetes is a non-communicable disease with metabolic dysfunction characterized by high glucose levels due to damage to pancreatic β cells so that insulin cannot be secreted normally by the body. Diabetes mellitus cannot be cured, but it can only be controlled with appropriate treatment. Most of the available synthetic antidiabetic treatments have serious side effects and are quite expensive. Therefore, traditional herbal medicine is an alternative which is used for some people in maintaining normal blood sugar levels. The use of herbal therapy with a combination of plant extracts has the potential to be more effective in lowering blood sugar when compared to single plant extracts. The aim of this article review is that to compile and provide a scientific overview of the various studies which have been conducted previously regarding the effectiveness of combinations of herbal plant extracts in diabetes mellitus. A comprehensive literature study was conducted by using various electronic search databases with the keyword “Combination of antidiabetic extracts” and 30 international research journals which were combined into review articles were obtained which shows that combinations of plant extracts proved to be more effective in lowering blood glucose levels compared to single herbal plant extracts.